Evaluation of ventricular repolarization features with novel electrocardiographic parameters (Tp-e, Tp-e/QT) in patients with psoriasis - Arısoy, Arif (Anatol J Cardiol, 2017)
OBJECTIVE: Psoriasis is a chronic inflammatory disorder, which affects around 1%–3% of the human population worldwide. Cardiovascular events are the leading cause of morbidity and mortality in patients with psoriasis. Some studies have reported that psoriasis is related to increased arrhythmias. The Tp-e interval and Tp-e/QT ratio have been accepted as new markers for the assessment of myocardial repolarization and ventricular arrhythmogenesis. The aim of this study was to assess ventricular repolarization in patients with psoriasis using Tp-e interval and Tp-e/QT ratio. METHODS: The study population consisted of 74 patients with psoriasis and 74 healthy volunteers. The diagnosis of psoriasis was based on a clinical or histopathological examination of all patients. QT interval, corrected QT (QTc), QT dispersion (QTd), Tp-e interval, corrected Tp-e, and Tp-e/QT ratio were measured from the 12-lead electrocardiogram. These parameters were compared between groups. RESULTS: According to the electrocardiographic parameters, QT and QTc intervals and QTd were significantly higher in patients with psoriasis than in control subjects (p<0.001; p<0.001; p=0.014; respectively). The Tp-e interval, corrected Tp-e, and Tp-e/QT ratio were significantly higher in patients with psoriasis than in control subjects [93±13 milliseconds (ms) vs. 98±14 ms, p=0.040; 104±17 ms vs. 111±17 ms, p=0.008; 0.23±0.03 vs. 0.25±0.03, p<0.001; respectively]. Additionally, the CRP value was an independent predictor of an increased Tp-e/QT ratio (β=0.537, p< 0.001). CONCLUSION: Our study revealed that ventricular repolarization features were impaired in patients with psoriasis. Therefore, these patients should be more closely screened for ventricular arrhythmias.